A constrained SSU-rRNA phylogeny reveals the unsequenced diversity of photosynthetic Cyanobacteria (Oxyphotobacteria) - Luc Cornet (BMC Research Notes, 2018)
Abstract Objective Cyanobacteria are an ancient phylum of prokaryotes that contain the class Oxyphotobacteria. This group has been extensively studied by phylogenomics notably because it is widely accepted that Cyanobacteria were responsible for the spread of photosynthesis to the eukaryotic domain. The aim of this study was to evaluate the fraction of the oxyphotobacterial diversity for which sequenced genomes are available for genomic studies. For this, we built a phylogenomic-constrained SSU rRNA (16S) tree to pinpoint unexploited clusters of Oxyphotobacteria that should be targeted for future genome sequencing, so as to improve our understanding of Oxyphotobacteria evolution. Results We show that only a little fraction of the oxyphotobacterial diversity has been sequenced so far. Indeed 31 rRNA clusters of the 60 composing the photosynthetic Cyanobacteria have a fraction of sequenced genomes < 1%. This fraction remains low (min = 1%, median = 11.1%, IQR = 7.3%) within the remaining “sequenced” clusters that already contain some representative genomes. The “unsequenced” clusters are scattered across the whole Oxyphotobacteria tree, at the exception of very basal clades. Yet, these clades still feature some (sub)clusters without any representative genome. This last result is especially important, as these basal clades are prime candidate for plastid emergence.